2018
DOI: 10.1111/sode.12341
|View full text |Cite
|
Sign up to set email alerts
|

To be fair, generous, or selfish: The effect of relationship on Chinese children’s distributive allocation and procedural application

Abstract: Previous research has found that children’s sharing with others relies on fairness norms, but also varies according to their social relationships. The current study focuses on the conflict between fairness and relationship, exploring their impacts across two resource allocation contexts. We used a parallel work task to explore the effect of relationship with different recipients (friend, stranger, or disliked peer) on three allocation patterns (generous, fair, or selfish), when children directly allocated reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…The difference is that previous studies have shown that Western children aged 3.5-11.5 years perpetuate resource inequality between two minimal groups (Olson et al, 2011). This may be because Chinese children pay more attention to the harmony of social relations than Western children and tend to allocate resources equally (Chai and He, 2017;Li et al, 2019). In addition to intergroup resource inequality without an explicit origin, intergroup inequality based on certain origins may have different effects on children's intergroup resource allocation (Olson et al, 2011;Shaw, 2016;Rizzo et al, 2020), which was examined in experiment 2.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The difference is that previous studies have shown that Western children aged 3.5-11.5 years perpetuate resource inequality between two minimal groups (Olson et al, 2011). This may be because Chinese children pay more attention to the harmony of social relations than Western children and tend to allocate resources equally (Chai and He, 2017;Li et al, 2019). In addition to intergroup resource inequality without an explicit origin, intergroup inequality based on certain origins may have different effects on children's intergroup resource allocation (Olson et al, 2011;Shaw, 2016;Rizzo et al, 2020), which was examined in experiment 2.…”
Section: Discussionmentioning
confidence: 95%
“…This may be because children tend to allocate resources equally to maintain harmony when there is no obvious clue to be used in resource allocation, and ingroup preference becomes a motivation for younger children's allocation. Nevertheless, children of different ages are both more likely to make allocations based on different clues when there are some explicit bases for allocation (Li et al, 2019;Xiao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We did not have strong predictions regarding the Best friend-Withhold condition. There is evidence suggesting Chinese and Western children act in a partial manner toward their own friends (i.e., direct friends) from about 4 to 12 years of age (Chen, Zhu, & Chen, 2013;Frederickson & Simmonds, 2008;Li, Curtis, Moore, Wang, & Zeng, 2019;Lu & Chang, 2016;Moore, 2009;Paulus, 2016;Paulus & Moore, 2014;Yu, Zhu, & Leslie, 2016). However, when recipients are described as the experimenter's friend (i.e., in-direct friend), 7-year-olds American avoid inequity and do not demonstrate a "partiality-bias" (Shaw & Olson, 2012).…”
Section: Study 1bmentioning
confidence: 99%